1997
DOI: 10.1590/s0100-40421997000300011
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem Molecular: Uma Ferramenta para o Planejamento Racional de Fármacos em Química Medicinal

Abstract: ISTRY. The molecular basis of modern therapeutics consist in the modulation of cell function by the interaction of microbioactive molecules as drug cells macromolecules structures. Molecular modeling is a computational technique developed to access the chemical structure. This methodology, by means of the molecular similarity and complementary paradigm, is the basis for the computer-assisted drug design universally employed in pharmaceutical research laboratories to obtain more efficient, more selective, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
20

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 42 publications
0
16
0
20
Order By: Relevance
“…A Química Medicinal, de caráter multidisciplinar, engloba áreas como a farmacologia, a bioquímica, a química orgânica sintética e a química computacional, entre outras, na busca do desenvolvimento/ descoberta de novos fármacos 1,2 . De forma geral, a aplicação da modelagem molecular na quími-ca medicinal vem seguindo abordagens "estáticas" centradas principalmente nos ligantes (fármacos, "lead-compounds", etc), sendo exemplos clássicos a SAR 3 e a QSAR 4 .…”
Section: Introductionunclassified
“…A Química Medicinal, de caráter multidisciplinar, engloba áreas como a farmacologia, a bioquímica, a química orgânica sintética e a química computacional, entre outras, na busca do desenvolvimento/ descoberta de novos fármacos 1,2 . De forma geral, a aplicação da modelagem molecular na quími-ca medicinal vem seguindo abordagens "estáticas" centradas principalmente nos ligantes (fármacos, "lead-compounds", etc), sendo exemplos clássicos a SAR 3 e a QSAR 4 .…”
Section: Introductionunclassified
“…Theoretical molecular modeling studies confirmed this possibility, indicating that the N-H group in C-5 and the 4-nitro moiety of the pyrazole ring have a medial distance of approximately 2Å, favoring the formation of H-bonding [44] able to introduce a certain degree of conformational strain and influencing the analgesic and antiedematogenic activity observed (Fig. 10).…”
Section: Molecular Hybridization As a Strategy For Planning New Antiimentioning
confidence: 88%
“…Nas últimas duas décadas, foram publicados artigos de revisão sobre QSAR/QSPR, 14,15 artigos abordando metodologias de QSAR/ QSPR, [16][17][18][19][20] e de suas aplicações, [21][22][23][24] além de revisões sobre modelagem molecular [25][26][27][28] em língua portuguesa. Contudo, não existe até o presente momento nenhum artigo científico que apresente a quimioinformática ao público acadêmico e científico em português.…”
Section: E Posteriormente Journal Of Chemical Information and Computerunclassified